Pengaruh Pengetahuan Keuangan, Sikap Keuangan, dan Kepribadian Terhadap Perilaku Manajemen Keuangan pada Pelaku UMKM Sentra Kerajinan Batik Desa Kunir Kidul - Abdul Afrillah Nur Sugeng; Afifudin Afifudin; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the effect of financial knowledge on financial management behavior in SMEs in batik craft centers in Kunir Kidul Village, to determine the effect of financial attitudes on financial management behavior in SMEs in batik craft centers in Kunir Kidul Village and to determine the influence of personality on financial management behavior in SMEs in the batik craft center in Kunir Kidul Village. The quantitative research approach is used in this study. The sample in this study were 45 permanent SMEs employees in Kunir Kidul Village, Lumajang Regency and the data processing used the SPSS data processing program. The validity and reliability tests were handled by this study. The classical assumption test, multiple linear regression test, statistical test and the coefficient of determination were employed in this study’s analysis. The variables used in this study are Financial Behavior, financial attitude, and personality which are independent variables, while the dependent variable in this study is financial management behavior.Keywords: Financial behavior, financial attitude, and personality